Leaflet repair and valve sparing (inclusion technique) aortic root repair: reference to the latest principles. (22nd April 2013) - Tucker, Adam; Parissis, Harry
Abstract : Up to 150 words summarising the case presentation and outcome (this will be freely available online). A Marfan case with dilated aortic root and prolapsed leaflets underwent aortic repair. The non-coronary leaflet-measured effective height was 7 mm (prolapsing) and was lifted up to 10 mm with a centrally placed plicating sutures. The right coronary leaflet had a geometric height of 17 mm (restricted) and was enlarged up to 21 mm with an autologous pericardial patch. The enlarged root was repaired with an inclusion technique. The final result showed a competent valve. This report outlines the feasibility of aortic repair provided  one adheres to the principles of aortic valve repair.